Analysis of the Legends of the Green Princess as Literature Teaching Materials with Local Wisdommelay Tribe in Teaching Materials High School - Abdullah Hasibuan; Nirmawan; Putri Juwita (PT Inovasi Pratama Internasional, 2022)
Literature is a form of one's ideas through a view of the social environment around him by using beautiful language. Literature is present as a result of the author's reflection on existing phenomena. Literature as a work of fiction with a deeper understanding, is not just an imaginary story or wishful thinking of the author, but a manifestation of the author's creativity in exploring and managing the ideas in his mind. This local wisdom is also owned by the North Sumatran Malay community through their folklore. In this folklore from North Sumatra, there is a legend, namely Putri Hijau with the value of local wisdom that is very strongly attached. In the current landscape of Indonesia, what is meant by